PENGARUH BELANJA PEMERINTAH DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN/KOTA DI PROVINSI KALIMANTAN SELATAN - RAHMAWATI RAHMAWATI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Rahmawati (2018). Effect of Government Expenditures on the Gross Regional Domestic Product of Regency / City in South Kalimantan Province. Advisor: M. Rusmin Nuryadin, SE, M.Si. This study was conducted to (1) Find out what's happening in the gross regional districts / municipalities in the province of South Kalimantan; (2) online factors that are more specific to the gross domestic product of the district / city in the province of South Kalimantan. The study was conducted in 13 districts/ cities in the province of South Kalimantan. Data is processed using panel data regression analysis with Fixed Effect Model (FEM) as the best model.Based on the analysis, the results of the study are simultaneously related to and a positive relationship between regional expenditure money to the GRDP of the district / city in the province of South Kalimantan. And in general it can be used for direct spending in the previous year has a very significant influence on the GRDP of districts / cities in South Kalimantan Province. Keywords: GRDP, direct shopping (direct shopping and indirect shopping).